Quality of Experience Playing Color Guard at Marching Band La Tansa Corps - Rahmat Suryo Samudro (Jurnal Pendidikan Tari, 2024)
The color guard requires body coordination, concentration, and mastery of equipment. Color guard performances are not just shown off, but are presented in the context of competition. Color guard players often feel adrenaline during the performance, but how performer manage this case through their experience. The quality of this symptom is analyzed using a scalpel from Jackson and Mihaly's perspective regarding the flow experience when playing color guard, especially the differences that appear during pre-performance and during the performance. So that the research does not spread in all directions, the researcher more specifically discusses research on the performance of the color guard in the La Tansa Coprs Marching Band at the 2023 Grand Prix Junior Band Championship and seek 2 performances before, which are 2017 Grand Prix Junior Band Championship and 2017 Grand Prix Marching Band Championship. The researcher uses direct observation to see the reality of what happened and explains it descriptively. The results of the research found that the quality of the La Tansa Corps Marching Band color guard players was able to create a great connection with the spectators through the performers' subjective experiences.